Building a Sport Tourism Hub in the Heart of Central Java: A Comprehensive Analysis of Surya Yudha Park Banjarnegara Development - SUBARA, Ari; PRANOTO, Pranoto (PT Keberlanjutan Strategis Indonesia, 2025)
This study analyzes the potential for developing Surya Yudha Park Banjarnegara as a leading sports tourism destination in Central Java. This qualitative research was conducted for three months (January-March 2025) using in-depth interview methods, participatory observation, and documentation studies of 11 key informants. The results of the study indicate that Surya Yudha Park has enormous strategic potential to develop into a sports tourism hub thanks to its strategic geographical position as the